Geostatistical Evaluation of Heavy Metals in of North-west India I I Indo-Gangetic Alluvial Plains - Grewal, M S; Dahiya, I S; Kuhad, M S (Annals of Arid Zone, 2016)
Spatial dependence of heavy metals like manganese (Mn), Nickel (Ni), Copper (Cu) and Cadmium (Cd) was measured using geostatistical technique in . large land areas of Indo~Gangetic alluvial plains. Four hundred and seventy soil samples were drawn at 10 km x 10 km grid nodes throughout Haryana State. The coefficient of variation of Mn, Ni, Cu and Cd were 44.52, 57.94, 48.77 and 61.95%, respectively. The variability of these metals was expressed by Exponential (Mn and Cd), Gausian (Ni) and Spherical (Cu) models. The estimates of mean by point kriging, block kriging and classical technique were more or less the same. The block kriging variances were 9.94 (Mn), 4.41 (Ni), 8.30 (Cu) and 6.67 (Cd) times less than the classical variances. The sample size by block kriging was very small compared to that in classical technique and point kriging methods.